THE ROLE OF AUDIO VISUAL MEDIA IN CREATING ACTIVE AND FUN ISLAMIC EDUCATION LEARNING - Maisaroh Ritonga; Wita Ferwati; Anggi Jelita Siregar; Dilla Rahmawati; Putri Arina; Selvy Agustin; Ermawati.S; Fitra Elia; Herliza (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The purpose of this study is to examine how audio-visual media can help improve engagement, motivation, and the quality of Islamic Religious Education (PAI) learning. By combining sound and images, the use of audio-visual media is considered capable of providing a more realistic learning experience, thereby helping students understand abstract ideas such as stories of goodness, religious practices, and moral principles. By interviewing three students, this study used a qualitative descriptive approach to learn their views on the performance of the media. The study has found that audio-visual media can create a more interesting and enjoyable classroom environment, in addition to helping students pay attention and understand information. When instructors play learning videos, animations, or audio recitations of the Quran, students become more motivated and active in the learning process. Concrete visualizations also help reduce verbosity and improve students' long-term retention of the subject matter. Therefore, audiovisual media has proven to be a powerful pedagogical tool for realizing interactive, dynamic, and relevant learning according to the characteristics of children in the digital era.